Gamma ray buildup factors for conventional shielding materials and buildup factors computed for tungsten with a thickness beyond 40 mean free paths. (December 2019) - Basu, Pew; Sarangapani, R.; Venkatraman, B.
Abstract: In this study, gamma ray buildup factors were investigated for conventional shielding materials such as lead, iron, concrete, and tungsten based on standard formulations in order to understand the variations between different formulations. The exposure buildup factors for 1 MeV gamma rays in lead, iron, and concrete for thicknesses beyond 40 mean free paths were computed using the modified geometric progression fitting formula and compared with previously reported data. For the first time, the exposure buildup factors were computed for tungsten at gamma ray energies from 15 keV to 15 MeV and for a penetration depth beyond 40 mean free paths. Highlights: Buildup factors with standard formulations for lead, iron, concrete, and tungsten. Exposure buildup factors for 1 MeV gamma rays in lead, iron, and concrete above 40 mfp. Exposure buildup factors for tungsten above 40 mfp at gamma ray energies from 15 keV to 15 MeV.